2005
DOI: 10.1073/pnas.0505148102
|View full text |Cite
|
Sign up to set email alerts
|

DNA and mRNA elements with complementary responses to hemin, antioxidant inducers, and iron control ferritin-L expression

Abstract: Ferritins, an ancient family of protein nanocages, concentrate iron in iron-oxy minerals for iron-protein biosynthesis and protection against oxy radical damage. Of the two genetic mechanisms that regulate rates of ferritin-L synthesis, DNA transcription and mRNA translation, more is known about mRNA regulation where iron targets complexes of an mRNA structure, the iron-responsive element (IRE) sequence, and ferritin IRE repressors (iron regulatory proteins 1 and 2). Neither the integration of mRNA and DNA reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 50 publications
4
149
0
Order By: Relevance
“…In some instances where cellular oxidative load is increased, cells may be more susceptible to iron mediated production of ROS and damage. We, along with others, demonstrated that ferritin is upregulated in response to a battery of different oxidative stressors [14,15,17]. Overexpression of ferritin H in cells reduced free iron levels and increased cellular resistance to H 2 O 2 toxicity [27,28].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In some instances where cellular oxidative load is increased, cells may be more susceptible to iron mediated production of ROS and damage. We, along with others, demonstrated that ferritin is upregulated in response to a battery of different oxidative stressors [14,15,17]. Overexpression of ferritin H in cells reduced free iron levels and increased cellular resistance to H 2 O 2 toxicity [27,28].…”
Section: Discussionmentioning
confidence: 86%
“…Our subsequent studies revealed an antioxidant responsive element (ARE) in the far upstream region of the promoter that is necessary for the transcriptional activation of the ferritin gene in response to various oxidative stressors, including H 2 O 2 , tBHQ (tertbutylhydroquinone), and hemin [14][15][16]. A similar ARE element was identified in ferritin L gene [17]. The ARE is a highly conserved enhancer element in various phase II genes involved in detoxification or with antioxidant properties, allowing for the activation of a battery of antioxidant genes including glutathione-S-transferases, NADH quinone oxidoreductase 1, and heme oxygenase 1 under chemical and oxidative stress conditions [18].…”
Section: Introductionmentioning
confidence: 75%
“…However heme was shown to be a strong inducer in some cellular systems: it acts by removing Bach1 repressor and permitting the binding of the transcription factor Nrf2 (Hintze and Theil 2006;Hintze et al 2007). Also oxidative stress induced a significant increase (up to 80 fold) in ferritin mRNA (Torti and Torti 2002;Hintze and Theil 2005). A combination of different repressor (Bach1 and ATF1) (Iwasaki et al 2007;Hintze et al 2007) and activators (Nrf2, JunD) (Iwasaki et al 2006;MacKenzie et al 2008) are involved in the recognition and binding of the Antioxidant Response Elements (ARE) in the promoter region of mouse ferritin H and L genes, modulating their expression in response to oxidative stimuli.…”
Section: Regulation Of Ferritin Expressionmentioning
confidence: 99%
“…27,28 In tissues, the antioxidant system comprises different enzymes, including superoxide dismutase, catalase and glutathione peroxidise, as well as substances such as ferritin, ascorbic acid, a-tocopherol, b-carotene, reduced glutathione, uric acid, biliverdin and bilirubin. [21][22][23][24][25][26]35 The sum of endogenous and food-derived antioxidants represents the total antioxidant activity of the system. The additive effect of all the different antioxidants provides greater protection against oxidative stress than any single compound alone.…”
Section: Total Anti-oxidant Capacity Assaymentioning
confidence: 99%
“…19 The pharmacological upregulation of the HO system has been shown to combat hypertension, inflammation and oxidative stress. [20][21][22][23][24][25][26] By breaking down the heme moiety, HO removes the pro-oxidant heme 21 while carbon monoxide, bilirubin/biliverdin and ferritin scavenge reactive oxygen species, inhibit lipid peroxidation and suppress tissue inflammation. [22][23][24][25][26] Accordingly, carbon monoxide, bilirubin, bliverdin and ferritin constitute a protective tetrad against hypertension and its secondary damages including oxidative and inflammatory insults.…”
Section: Introductionmentioning
confidence: 99%